2018
DOI: 10.18502/sjms.v13i2.2640
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Diffuse Hair Fall Case Due to Vitamin D Deficiency: A Case Report and Literature Review

Abstract: A 45-year-old female from northern Sudan presented a complaint of diffuse hair loss from her scalp for 4 years. The condition started when she was in Saudi Arabia, where she resided for five years with her husband and children. The condition is associated with fatigability and easily falling asleep. The condition is static with no known relieving or aggravating factors. She looks well, not pale, jaundiced or cyanosed, regular pulse, no lymph node enlargement; thyroid is central with normal size and no lower li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These results lead to the conclusion that these patients share a diagnosis of non-scarring alopecia associated with vitamin D deficiency. 6,7 In all three case reports, hair regrowth was associated with supplementation of vitamin D in the absence of other medical or surgical interventions. But if vitamin D deficiency caused hair thinning in these case reports, it begs the questions, does it always cause hair loss?…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results lead to the conclusion that these patients share a diagnosis of non-scarring alopecia associated with vitamin D deficiency. 6,7 In all three case reports, hair regrowth was associated with supplementation of vitamin D in the absence of other medical or surgical interventions. But if vitamin D deficiency caused hair thinning in these case reports, it begs the questions, does it always cause hair loss?…”
Section: Discussionmentioning
confidence: 94%
“…4,5 Specifically, correction of vitamin D deficiency has been observed in at least two previous published case reports to result in reversal of hair thinning in female patients with no other cause for hair loss. 6,7 For decades it has been known that genetic mutations which cause an abnormal vitamin D receptor, usually manifested by various degrees of resistance to vitamin D, often result in alopecia being displayed in affected infants. Research has established the vitamin D receptor as integral to initiating anagen and hair follicle cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ruiz-Tagle et al reported association of TE with defi ciencies of iron, zinc, and vitamin D and recommended supplementation of vitamin D at a dose rate of 50,000 IU/wk and 800 to 2,000 IU/wk as maintenance dose to avoid recurrence of CTE (6). Suad and Modawe reported successful decrease of hair loss in a woman treated with vitamin D 3 50,000 IU/wk and 1,000 IU/wk as maintenance dose (7).…”
mentioning
confidence: 99%